Effect of Glucosamine Sulfate Alone and Combined with Moderate Intensity Exercise on Serum Levels of CS 846 Epitope and Cartilage Oligomeric Matrix Protein in a Rat Model of Osteoarthritis - babak Biniaz; hajar abaszadeh; parvin farzanegi (Medical Laboratory Journal, 2021)
Background and objectives: Osteoarthritis is the result of a defect in synovial membrane-covered joint tissues. The purpose of this study was to investigate effects of glucosamine sulfate alone and combined with moderate intensity exercise on serum levels of CS 846 epitope and cartilage oligomeric matrix protein (COMP) in a rat model of osteoarthritis. Methods: In this study, after inducing osteoarthritis in 42 male Wistar rats (weighting 250±300 g, aged 8 to 12 weeks), the rats were randomly divided into five groups: control-healthy, control-patient, patient-exercise, patient-glucosamine and patient-glucosamine-exercise. The training program consisted of 30 minutes of running on a non-slip treadmill at speed of 16 m/min in the first week with progressive overload principle reaching 50 minutes by the eighth week. The glucosamine groups received oral glucosamine sulfate (250 mg/kg/day) once a day for eight consecutive weeks. The serum levels of CS 846 epitope and COMP were measured using commercial ELISA kits. Data were analyzed using one-way ANOVA and Tukeychr('39')s post hoc test. All statistical analyses were performed in GraghPad prism 8 and at significance level of 0.05. Results: Combined exercise and glucosamine supplementation caused a significant decrease in the COMP and CS846 levels. This decrease was more profound compared to that of glucosamine and exercise alone. Conclusion: Overall, the findings of the present study showed that osteoarthritis increases serum COMP and CS 846 levels. In addition, glucosamine supplementation combined with exercise can significantly improve knee osteoarthritis in rats.